Students’ Perceptions of Using Social Media as a Tool for Learning Arabic at UINSI Samarinda - Salsabila, Adinda Rana; Aprianti, Anindya Putri; Wahdania, Asdelia; Nuriman, Kurnia Masyita; Adawiyah, Rabiatul; Fadhilah, Alya Nur (Borneo Journal of Language and Education, 2023)
This study aims to explore students’ perceptions at UINSI Samarinda regarding the use of social media as a tool for learning Arabic. The phenomenon under investigation arises from the increasing utilization of digital platforms by students, alongside the challenges they encounter in optimizing social media for language learning. A qualitative phenomenological approach was employed, focusing on students’ experiences and subjective meanings. Data were collected through semi-structured interviews, participatory observation, and documentation of learning materials on social media, involving 15 students from the Arabic Language Study Program selected using purposive and snowball sampling techniques. Data were analyzed thematically using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings revealed three primary themes: (1) ease of access and learning flexibility, as students used social media to study at different times and locations; (2) motivation and active engagement, with social interactions and feedback from peers and native speakers enhancing participation and learning interest; and (3) challenges and obstacles in online learning, such as distractions from entertainment content and difficulties understanding materials without direct guidance. These findings reinforce social constructivist and digital literacy theories in language learning while highlighting Indonesian students’ subjective experiences, which have rarely been examined qualitatively. This study has practical implications for developing structured, social media–based learning strategies and for institutional policies on integrating digital platforms into the curriculum. Further research is recommended to explore the relationships between digital literacy, learning motivation, and the effectiveness of social media across various Islamic higher education contexts.